Adaptive PI control with robust variable structure anti-windup strategy for systems with rate-limited actuators: Application to compression systems. (March 2020) - Eldigair, Yousif; Garelli, Fabricio; Kunusch, Cristian; Ocampo-Martinez, Carlos
Abstract: In this paper, an adaptive proportional–integral (PI) control strategy for nonlinear systems with constrained actuators is discussed. In particular, a variable-structure anti-windup strategy that can be retrofitted onto different control structures is proposed and validated. Both the developed controller and anti-windup method are attuned to an automotive industrial control application: the control of air mass flow-rate and pressure in a fuel cell system using a high speed turbo-compressor and an electromechanical valve. Both the compressor and valve are rate-limited. The results from experimental tests agree with the simulations obtained and showing the effectiveness of the proposed approach by evidencing the fast control dynamics and the proper and desired closed-loop performance of the scheme without windup phenomena.